Alexithymic traits, mental and physical health, and early-life adversity – FinnBrain birth cohort study - Kajanoja, Jani (fi=Turun yliopisto|en=University of Turku|, 2019)
Alexithymia is a personality construct first identified in hospitalized psychosomatic patients. It is characterized by difficulties in identifying (DIF) and describing (DDF) feelings, an externally oriented, or concrete and pragmatic thinking style (EOT), as well as a scarcity of fantasy and imagination. Alexithymia has been associated with increased psychiatric and somatic morbidity across diagnostic categories, as well as increased markers of physiological stress. The etiology of alexithymia is unclear although childhood environmental influences are likely to play a role in it. Several studies imply that alexithymia is a heterogeneous phenomenon with possible subtypes that have differential associations with mental health and emotion regulation. This dissertation is part of the FinnBrain Birth Cohort Study, in which we analyzed a large sample of fathers and mothers and compared their alexithymic traits with mental and physical health outcomes, as well as self-reported early-life adversities in childhood. Our results support the hypotheses of the existence of two alexithymia subtypes: One characterized by high levels of DIF, as well as increased depressive and anxiety symptoms; and another characterized by high levels of EOT, exhibiting lower psychiatric symptomatology. However, EOT, even while not increasing the risk for mood or anxiety symptoms, was associated with increased substance use in men, and a higher BMI and higher prevalence of gestational diabetes in women. In pregnant women, alexithymic traits, and especially the dimension of DIF, was additionally associated with higher hair cortisol concentrations during late pregnancy, indicating heightened levels of chronic stress. Regarding early-life adversity, we showed that alexithymia was specifically related to childhood experiences of emotional neglect and was associated with adult attachment insecurity. These findings show that alexithymic traits have differential associations with psychiatric symptomatology, substance use and metabolic health. Importantly, they show that many of these associations are independent of mood and anxiety. Findings on early-life adversity in alexithymia imply that depression with concurrent alexithymia may represent a specific subtype of depression, treatment of which may benefit from a focus on childhood emotional neglect and attachment insecurity.

Aleksitymia kuvaa moniulotteista persoonallisuuden piirteistöä, jonka tunnusmerkkejä ovat vaikeudet tunteiden tunnistamisessa ja ilmaisussa, mielikuvituksen köyhyys sekä ulkokohtainen ajattelutyyli, jossa kiinnostus sisäiseen maailmaan ja tunteisiin on vähäistä. Aleksitymia on liitetty moniin somaattisiin ja psyykkisiin terveysongelmiin, sekä fysiologiseen stressiin. Useat tutkimukset viittaavat siihen, että aleksitymiaa ei voida pitää yksiulotteisena ilmiönä, vaan sillä on useita alatyyppejä, joilla saattaa olla erilaisia vaikutuksia terveyteen ja tunnesäätelyyn. Aleksitymian syntymekanismit ovat edelleen epäselviä, mutta lapsuuden ympäristöllä ja vastoinkäymisillä ajatellaan olevan merkittävä rooli sen kehittymisessä. Tämä tutkimus on osa FinnBrain syntymäkohorttitutkimusta. Tutkimusaineisto koostuu suuresta otoksesta isiä ja äitejä. Tutkimme tässä populaatiossa aleksityymisten piirteiden yhteyttä fyysiseen terveyteen, mielenterveyteen sekä lapsuuden vastoinkäymisiin. Löydöksemme tukevat hypoteeseja aleksitymian kahdesta alatyypistä: Ensimmäistä alatyyppiä luonnehtivat subjektiivinen vaikeus tunnistaa ja ilmaista tunteita, sekä lisääntynyt masennus- ja ahdistuneisuusoireisto. Toisessa alatyypissä korostuneempana on ulkokohtainen ajattelutyyli, eikä siihen liity lisääntynyttä psykiatrista oireilua. Ulkokohtainen ajattelutyyli kuitenkin lisäsi alkoholin ja tupakan kulutusta miehillä, sekä oli yhteydessä ylipainoon ja raskausdiabetekseen naisilla, riippumatta samanaikaisista masennus- ja ahdistusoireista. Raskaana olevilla naisilla aleksitymia oli lisäksi yhteydessä korkeampiin hiusten kortisolitasoihin, mikä viittaa krooniseen stressiin. Lapsuuden vastoinkäymisten osalta löydöksemme viittaavat siihen, että aleksitymia on yhteydessä lapsuuden emotionaaliseen vaille jäämiseen sekä kiintymyssuhdeongelmiin. Löydökset korostavat aleksitymian monimuotoisuutta, ja osoittavat, että aleksitymian eri ulottuvuudet ovat yhteydessä erilaisiin terveysongelmiin sekä päihteidenkäyttöön. Nämä yhteydet ovat lisäksi riippumattomia samanaikaisista masennus- ja ahdistuneisuusoireista. Löydökset liittyen lapsuuden vastoinkäymisiin aleksitymian taustalla korostavat emotionaalisen vaille jäämisen ja kiintymyssuhdeongelmien tärkeyttä, ja voivat auttaa uusien hoitomuotojen kehittämisessä psykiatrisille potilaille, joilla on aleksityymisiä piirteitä